Impact of Core Cell Size on Selected Properties of Honeycomb Paperboard - Gabriela Kmita-Fudalej; Grzegorz Jasiński; Zbigniew Kołakowski (BioResources)
The effect of the cell size of honeycomb paperboard core was studied relative to the grammage (basis weight) and two key strength properties of cellular paperboard: bending stiffness (BS) and flat crush resistance (FCT). The subject of the study was honeycomb paperboard of a different structure, in which single-layer kraftliner paper was used for the flat layers, with a grammage and thickness lower than the paper used for the paperboard core. Five paperboards made of the same fibrous materials of the same thickness and different core cell diameter D were tested, equal to 10, 12, 14, 17, and 22 mm, respectively. The research showed a close dependence of the grammage of the paperboard, BS, and the FCT of the honeycomb paperboard on the core cell size. With the increase of the core cell size, the above-mentioned physical properties showed a decreasing trend. For the honeycomb paperboards tested, a linear relationship was obtained between the grammage, BS, FCT of the honeycomb board and the diameter D of the hexagonal core cell.